2021
DOI: 10.4049/jimmunol.2100362
|View full text |Cite
|
Sign up to set email alerts
|

Self-Renewing Islet TCF1+ CD8 T Cells Undergo IL-27–Controlled Differentiation to Become TCF1− Terminal Effectors during the Progression of Type 1 Diabetes

Abstract: Author contributions: A.E.C. and D.M.S. designed experiments, performed experimental work, analyzed results, prepared figures, and wrote the manuscript. B.F. performed experimental work and provided intellectual contribution. G.P. provided critical cell sorting expertise. M.Y.K. analyzed single-cell RNA sequencing (scRNA-seq) data and revised the manuscript. C.-W.L. analyzed the scRNA-seq data. R.B. generated gene regulatory network models. W.R.D. provided reagents and intellectual contribution. W.C. and Y.-G.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 93 publications
10
22
0
Order By: Relevance
“…Regulon analysis predicted enriched activity of TCR signaling-induced TFs such as Nfkb1 and Jun ( Courtney et al, 2018 ) in recently activated islet CD8 T cells as would be expected. In addition, recently activated, bystander, and progenitor cells in the islets all had high predicted activity of Stat3, a TF downstream of IL-27 signaling; this is supported by our recent work showing that IL-27 signaling promotes progenitor to effector CD8 T-cell differentiation in the islets of NOD mice ( Ciecko et al, 2021 ). Conversely, islet effector cells exhibited increased activity of TFs associated with aerobic glycolysis, such as Hif1a ( Shi et al, 2011 ) and Foxk2 ( Sukonina et al, 2019 ); aerobic glycolysis is crucial for the effector function of activated T cells ( Gupta et al, 2020 ), and we have found that Hif1a is also up-regulated in effector-like tumor-infiltrating lymphocytes ( Topchyan et al, 2021 ).…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…Regulon analysis predicted enriched activity of TCR signaling-induced TFs such as Nfkb1 and Jun ( Courtney et al, 2018 ) in recently activated islet CD8 T cells as would be expected. In addition, recently activated, bystander, and progenitor cells in the islets all had high predicted activity of Stat3, a TF downstream of IL-27 signaling; this is supported by our recent work showing that IL-27 signaling promotes progenitor to effector CD8 T-cell differentiation in the islets of NOD mice ( Ciecko et al, 2021 ). Conversely, islet effector cells exhibited increased activity of TFs associated with aerobic glycolysis, such as Hif1a ( Shi et al, 2011 ) and Foxk2 ( Sukonina et al, 2019 ); aerobic glycolysis is crucial for the effector function of activated T cells ( Gupta et al, 2020 ), and we have found that Hif1a is also up-regulated in effector-like tumor-infiltrating lymphocytes ( Topchyan et al, 2021 ).…”
Section: Resultssupporting
confidence: 58%
“…(A) Colors correspond to the clusters shown in (A). (A, D) Dot plot showing module scores within each cluster from (A) of the top 100 differentially expressed genes in the four CD8 T cell clusters previously identified in non-obese diabetic islets ( Ciecko et al, 2021 ). (D, E) As in (D), but using the top 100 differentially expressed genes among previously identified splenic CD8 T cell clusters from LCMV Clone 13 infection ( Zander et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations